Infants' Fast Neural Categorization of Artificial Objects: The Impact of Stimulus and Task Characteristics. - Pauen, Sabina; Peykarjou, Stefanie (Developmental Psychology, 2023)
This study explores how 7-month-old infants categorize graphical images varying in basic perceptual features by using a fast periodic visual stimulation (FPVS) task. Most participants were Caucasian and their parents had a higher education, but the family's socioeconomic background was mixed. Experiment 1 (N = 23) tested brain responses to configurational versus scrambled image sequences and found an oddball effect for both conditions, with configurational information leading to stronger neural responses. Experiment 2 explored the role of category learning for later FPVS performance: Group A (control; n = 22) participated in the FPVS categorization task only. Group B (fam; n = 21) was first familiarized with standard exemplars. Group C (fam + contrast; n = 29) was presented an additional exemplar of the contrasting category before the FPVS task. Electroencephalogram analyses revealed a decrease in Nc amplitude (measuring attention) throughout the familiarization phase. Long looking at the out-of-category exemplar in Group C indicated infants' visual interest. Brain responses in the subsequently presented FPVS were strong but did not differ between groups. This highlights the ability of the infant brain to organize perceptual input very rapidly without requiring familiarization but also points to the need for further studies exploring brain processes associated with infants' category learning and categorization at the brain level. Public Significance Statement: Within milliseconds, the brain of 7-month-old infants categorized artificial objects based on low-level perceptual features, but responses were stronger when additional configurational information was provided. A familiarization with the standard category led to neural adaptation and to visual interest in a subsequently presented out-of-category exemplar, but this experience did not affect categorization in a FPVS task, thus pointing to the need of more studies exploring the mechanisms underlying infant categorization.